The Effect of Service Quality, AI Service Quality, Green Banking Practices, and Shariah Compliance on Customer Loyalty, with Customer Satisfaction as a Mediating Variable, in Islamic Banking in East Kalimantan - Hana Hayati; Setiawan; Dwi Suhartanto (Cv. Syntax Corporation Indonesia, 2026)
The development of digital technology, especially the use of Artificial Intelligence (AI), has driven the transformation of banking services through increasing efficiency, personalization, and the quality of customer interactions. However, in Islamic banking, the optimization of digital services has not been fully balanced with increasing customer satisfaction and loyalty, especially related to service quality, sharia compliance, and green banking practices. This study aims to analyze the influence of service quality, AI service quality, green banking practices, and shariah compliance on the satisfaction and loyalty of Islamic bank customers in East Kalimantan. This study uses a quantitative method with an explanatory design through a survey of 200 respondents and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of the study show that service quality, AI service quality, and shariah compliance have a significant effect on customer satisfaction, while green banking practices have no significant effect. In addition, customer satisfaction has been proven to have a significant effect on customer loyalty. The results of the Multi-Group Analysis (MGA) show that the model applies consistently across gender, age, and length of customer service, thus showing the generalizability of the findings among Islamic banking customers in East Kalimantan. This research is expected to help Islamic banking in improving service quality, developing AI-based services, and strengthening the application of sharia principles to increase customer satisfaction and loyalty. In addition, this research also makes a theoretical contribution to the development of the Stimulus-Organism-Response (SOR) model in the context of Islamic banking and digital technology.